2023
DOI: 10.1002/vetr.2834
|View full text |Cite
|
Sign up to set email alerts
|

Opportunistic viral surveillance confirms the ongoing disease threat grey squirrels pose to sympatric red squirrel populations in the UK

Abstract: Background: Red Squirrels United was a UK landscape-scale grey squirrel management programme undertaken between 2016 and 2020. Methods: A total of 11034 grey squirrels were removed by culling, with 1506 necropsied and 1405 suitable for adenovirus (AdV) or squirrelpox virus (SQPV) quantitative PCR (qPCR) analysis. Spleen, lip or hair were extracted, and DNA was isolated, with samples tested in duplicate by qPCR. Results: Of 1378 tissue samples, 43% were positive for AdV and 10% for SQPV. Of 1031 hair samples, 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 46 publications
(122 reference statements)
0
1
0
Order By: Relevance
“…In Europe, chipmunk genotype I was first reported in two Eurasian red squirrels ( Sciurius vulgaris ) in Italy [ 21 ]. Eastern gray squirrels and native Eurasian red squirrels are sympatric species in the UK and Italy [ 22 , 23 ], most likely due to the introduction of the eastern gray squirrel into Europe during the last century. Prediger et al [ 24 ] demonstrated that eastern gray squirrels introduced in northern Italy are parasitized with chipmunk genotype I.…”
Section: Introductionmentioning
confidence: 99%
“…In Europe, chipmunk genotype I was first reported in two Eurasian red squirrels ( Sciurius vulgaris ) in Italy [ 21 ]. Eastern gray squirrels and native Eurasian red squirrels are sympatric species in the UK and Italy [ 22 , 23 ], most likely due to the introduction of the eastern gray squirrel into Europe during the last century. Prediger et al [ 24 ] demonstrated that eastern gray squirrels introduced in northern Italy are parasitized with chipmunk genotype I.…”
Section: Introductionmentioning
confidence: 99%